Postsekularyzm między Wschodem i Zachodem - Obirek, Stanisław (Humaniora. Czasopismo Internetowe, 2023)
The aim of the article Postsecularism between East and West is to present the paradigm shift in understanding the place of religion in public space in recent decades. The term that aptly describes this change is postsecularism. The prefix “post” is more than just an indication of a new quality of “secularism.” In fact, it marks a revolutionary change in understanding the traditionally opposing concepts of secularism and religion. The article presents this process in three stages. First, it describes the theological turn that has taken place in recent decades, primarily in Catholic theology, then it points to the place of literature in theological reflection and finally presents the surprising contribution of the mathematical concept (fractal) in overcoming the impasse in which interreligious dialogue found itself.